2023
DOI: 10.1212/nxi.0000000000200122
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Profile in 75 Patients With Anti–Myelin-Associated Glycoprotein Neuropathy

Abstract: Background and ObjectivesNeuropathy with antibodies to myelin-associated glycoprotein (MAG) is the most common paraproteinemic IgM neuropathy. Recently, the mutational profile of theMYD88andCXCR4genes has been included in the diagnostic workup of IgM monoclonal gammopathies. The objective of our study was to assess the prevalence ofMYD88L265PandCXCR4S338Xgene variants in patients with anti-MAG antibody neuropathy. Secondary aims were to evaluate possible correlations between the mutational profile and neuropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Furthermore, mutations in MYD88 enhanced BTK expression 40 . The MYD88 mutation was detected in 80%–100% of WM cases 41 and in >60% of anti‐MAG neuropathy cases, 42,43 indicating that BTK inhibitors might have a therapeutic effect. BTK inhibitors include first‐generation ibrutinib and second‐generation selective BTK inhibitors, such as acalabrutinib, zanubrutinib and tirabrutinib.…”
Section: Igm‐type Panmentioning
confidence: 99%
“…Furthermore, mutations in MYD88 enhanced BTK expression 40 . The MYD88 mutation was detected in 80%–100% of WM cases 41 and in >60% of anti‐MAG neuropathy cases, 42,43 indicating that BTK inhibitors might have a therapeutic effect. BTK inhibitors include first‐generation ibrutinib and second‐generation selective BTK inhibitors, such as acalabrutinib, zanubrutinib and tirabrutinib.…”
Section: Igm‐type Panmentioning
confidence: 99%
“…In the study by Svahn and colleagues, 11 approximately 68% had monoclonal gammopathy of unknown significance (MGUS), 29% had Waldenström's macroglobulinemia, and 3% had chronic lymphocytic leukemia or B-CLL. Castellani and colleagues reported that 66.7% of 75 patients tested had a mutation in MYD88, more often in macroglobulinemia 47 48 making them susceptible to treatment with Bruton tyrosine kinase inhibitors.…”
Section: Introductionmentioning
confidence: 99%